Acute Unilateral Blindness from Superior Ophthalmic Vein Thrombosis: A Rare Presentation of Nephrotic Syndrome from Class IV Lupus Nephritis in the Absence of Antiphospholipid or Anticardiolipin Syndrome - Baidoun, Firas; Issa, Rommy; Ali, Robert; Al-Turk, Bashar (Case Reports in Hematology, 2015)
Patients with systemic lupus erythematosus (SLE) are at high risk of arterial and venous thrombosis secondary to anti-phospholipid antibodies. Herein, we are presenting an interesting case of venous thrombosis in a patient with SLE in the absence of anti-phospholipid antibodies.